Analisis Ketuntasan Hasil Belajar Ranah Kognitif Mahasiswa Pada Perkuliahan Gelombang dan Optik Dengan Menggunakan Media Simulasi PhET - Hikmawati Hikmawati; Kosim Kosim; Syahrial Ayub (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to analyze the mastery of learning outcomes in the cognitive domain of students in Waves and Optics lectures using PhET simulation media. This pre-experimental research is a quantitative descriptive study. The research subjects consisted of 14 students in class IVB who took the Waves and Optics course in the Even Semester of 2023. The lectures were held in 6 meetings, from 16 February to 30 March 2023. The research instrument used a written test in the form of an essay which was given after the lecture had used PhET simulation media. The percentage of completeness of students' cognitive learning outcomes is obtained by dividing the total score by the maximum score multiplied by 100%. Students are declared to have completed their learning outcomes (individual completeness) if they have reached a score of 75 as the limit for mastery of the material, while classical completeness in this study determined that a class is said to have completed learning if in that class there are more than 80% of students who have completed their studies. The results showed that the average student score was 81 (grade conversion was B+). The lowest score is 70 (grade conversion is C+), while the highest value is 90 (grade conversion is A). Of the 14 students, there were 2 students whose learning outcomes were declared incomplete. Thus, the percentage of students' cognitive learning outcomes in the Waves and Optics course is declared classically completed by 86%. PhET simulation media can be an alternative learning media to help students master the physics concepts of waves and optics